2017
DOI: 10.1080/15384101.2017.1395534
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 regulates tongue cancer cells proliferation, apoptosis and invasion

Abstract: Our results prove that the oncogenic role of Notch1 in tongue cancer and provide the direction of targeted therapy of tongue cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 31 publications
3
46
0
3
Order By: Relevance
“…NOTCH1 is involved in the regulation of the Akt/mTOR signaling pathway (46,47), which is widely acknowledged to promote cancer development (22)(23)(24)(25)(26)42). The present study revealed that shHSP27 decreased NOTCH1 expression, indicating that HSP27 might regulate chemoresistance in colon cancer cells via NOTCH1 and that NOTCH1 might regulate of HSP27 in the Akt/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…NOTCH1 is involved in the regulation of the Akt/mTOR signaling pathway (46,47), which is widely acknowledged to promote cancer development (22)(23)(24)(25)(26)42). The present study revealed that shHSP27 decreased NOTCH1 expression, indicating that HSP27 might regulate chemoresistance in colon cancer cells via NOTCH1 and that NOTCH1 might regulate of HSP27 in the Akt/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, cross-talk among the notch receptor 1 (NOTCH1), mTOR and PI3K/Akt signaling pathways is associated with apoptosis (21). The binding of NOTCH1 to its ligands allows DNA-binding proteins to regulate the expression of NOTCH1 target genes, which are involved in the proliferation, differentiation and apoptosis of various tumor cells (22)(23)(24). Additionally, PI3K and its effectors, including Akt and mTOR, play a key role in the proliferation and survival of tumor cells (25).…”
Section: Introductionmentioning
confidence: 99%
“…There are 41 genes with the most hemimethylation in tumor DNA, see Table 9. Among these genes, TP73 [18][19][20], GNAS [21][22][23][24][25], and NOTCH1 [26,27] are notable ones with known relations to cancer. Table 9 shows that among these 41 genes, 1 is a tumor suppressor (WT1), 3 are oncogenes (GNAS, NOTCh1, and PRDM16), and of those 3, 2 are translocated cancer genes (NOTCH1 and PRDM16).…”
Section: Resultsmentioning
confidence: 99%
“…Notch1, a member of the Notch receptors, was predicted as a novel direct target gene of miR-495 in OSCC in the present study. Notch1 was reported to be overexpressed in OSCC, which was correlated with the T-stage, clinical stage, differentiation, lymph node metastasis, depth of invasion and locoregional recurrence (27)(28)(29). Notch1 activation has been reported to promote OSCC cell proliferation, apoptosis, migration, invasion and EMT (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…3A). Notch1 was previously reported to be involved in the onset and progression of OSCC (27)(28)(29)(30)(31) and was therefore selected as a candidate for further confirmation in the present study. A luciferase reporter assay was performed to determine whether the 3'-UTR of Notch1 may be directly targeted by miR-495.…”
Section: Overexpression Of Mir-495 Prohibits the Proliferation And Inmentioning
confidence: 99%